Cancer, genetic susceptibility and risk of coronary artery disease: A prospective study - Yidan Wang; Shan Zhong; Na Sun; Yunfei Wu; Jun Lyu; Minghui Piao; Wenbo Qu; Xueyu Wang; Wenjun Ni; Xia Gu; Tianshu Han; Jinwei Tian (American Journal of Preventive Cardiology)
Objective: Cancer survivors have an increased risk of developing coronary artery disease (CAD). We introduce CAD polygenic risk scores (PRS) and examine associations with cancer status on CAD outcomes. Methods: From the UK Biobank, we identified cancer survivors and CAD outcomes among 464,193 CAD-free participants using linked cancer registries, hospitalizations, and death records. CAD-PRS was categorized as low (lowest tertile), intermediate (tertile 2), and high (highest tertile). Adjusted Cox models assessed the joint and interaction effects of cancer status and CAD-PRS on CAD outcomes. Results: Over the follow-up (median 11.7 years), 36,332 participants developed CAD. Compared to low CAD-PRS, the hazard ratios (HRs) and 95% confidence intervals (CIs) for CAD was 1.35 (1.31–1.38) for intermediate and 1.86 (1.81–1.91) for high CAD-PRS. The HR (95% CI) for CAD in cancer survivors was 1.16 (1.13–1.19) compared to those without cancer. In the joint effect analysis, compared to participants with low CAD-PRS and no cancer, the HRs (95% CIs) for CAD were 1.37 (1.32–1.41) and 1.90 (1.84–1.96) for intermediate and high CAD-PRS without cancer, respectively. For those with cancer, the HRs (95% CIs) were 1.26 (1.19–1.33), 1.59 (1.51–1.67), and 2.13 (2.03–2.23) for low, intermediate, and high CAD-PRS, respectively. A significant multiplicative interaction (HR: 0.94, 95% CI: 0.91–0.98) was observed between CAD-PRS and cancer status on CAD. Additionally, a significant additive interaction between cancer and high CAD-PRS was found for fatal CAD. Conclusion: Cancer was associated with a higher risk of CAD and may further increase the risk of CAD related to genetic factors.